2002
DOI: 10.1136/pmj.78.919.273
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the corrected QT interval and corrected QT dispersion during haemodialysis

Abstract: The link between increased QT dispersion and cardiac death in subjects with diabetes and arterial disease is well recognised. Corrected QT dispersion was studied in subjects with end stage renal failure on haemodialysis. Thirty one stable, chronic subjects on haemodialysis had 12-lead electrocardiograms (ECGs) taken before and after a single haemodialysis session. The QT interval was measured manually in each and the corrected QT and corrected QT dispersion calculated. Serum concentrations of potassium, calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
5
25
1
Order By: Relevance
“…Changes of serum calcium affect the electrical conduction times of the myocardium, increase the re-entry or triggered activity [3]and may lead to the increase in the dispersion of the action potential. In our trial, the predialysis calcium level was the independent factor that inversely affected the durations of predialysis dispersion parameters and the dialysis induced prolongation of QT-c-D and Tpe-c-D. Our study confirms most of the previous observations that low calcium concentration prolongs QT dispersion parameters in HD patients [12, 13, 16, 18], though Yildiz et al [15]and Howse [27]in their studies have not found such a relation. The lack of relations between potassium or calcium levels in the studies of other authors may result from the fact that other important factors have influenced dispersion parameters, such as diabetes, congestive heart disease and ischaemic heart disease.…”
Section: Discussionsupporting
confidence: 90%
“…Changes of serum calcium affect the electrical conduction times of the myocardium, increase the re-entry or triggered activity [3]and may lead to the increase in the dispersion of the action potential. In our trial, the predialysis calcium level was the independent factor that inversely affected the durations of predialysis dispersion parameters and the dialysis induced prolongation of QT-c-D and Tpe-c-D. Our study confirms most of the previous observations that low calcium concentration prolongs QT dispersion parameters in HD patients [12, 13, 16, 18], though Yildiz et al [15]and Howse [27]in their studies have not found such a relation. The lack of relations between potassium or calcium levels in the studies of other authors may result from the fact that other important factors have influenced dispersion parameters, such as diabetes, congestive heart disease and ischaemic heart disease.…”
Section: Discussionsupporting
confidence: 90%
“…Heart disease free individuals with CKD are thus at an increased risk for ventricular arrhythmias. These findings are concordant with the conclusions revealed by other studies suggesting that renal disease renders the heart more vulnerable to electrical disturbances [30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…12 Another study found no correlation between QT dispersion and reduction in serum potassium and magnesium during hemodialysis. 13 The other biochemistry findings in our study were as expected in end-stage renal failure.…”
Section: Resultssupporting
confidence: 87%